2013
DOI: 10.1242/bio.20135173
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminus of S. pombe DDK subunit Dfp1 is required for meiosis-specific transcription and cohesin cleavage

Abstract: SummaryThe DDK complex is a conserved kinase complex, consisting of a catalytic subunit, Hsk1 (Cdc7), and its regulatory subunit Dfp1 (Dbf4). This kinase is essential for DNA replication. In this work, we show that dfp1-r35, which truncates the Dfp1 C-terminus zinc finger, causes severe meiotic defects, including reduced spore viability, reduced formation of programmed double strand breaks, altered expression of meiotic genes, and disrupted chromosome segregation. There is a high frequency of dyad formation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 70 publications
(141 reference statements)
3
32
0
Order By: Relevance
“…The eponymous DBF4 protein is an activator of the CDC7 serine/threonine kinase, which has a conserved role in DNA replication initiation from yeast to humans (Hughes et al 2012). In yeast, the dbf4/cdc7 complex was moreover linked to chromosome segregation during meiosis (Kovacikova et al 2013;Le et al 2013). Coincidently, we found that Liz expression peaks at meiosis during mouse spermatogenesis, and canonical Zdbf2 is highly transcribed in the oocyte, leading to the exciting possibility that Zdbf2 may fulfill meiotic roles in mammals.…”
Section: Discussionmentioning
confidence: 73%
“…The eponymous DBF4 protein is an activator of the CDC7 serine/threonine kinase, which has a conserved role in DNA replication initiation from yeast to humans (Hughes et al 2012). In yeast, the dbf4/cdc7 complex was moreover linked to chromosome segregation during meiosis (Kovacikova et al 2013;Le et al 2013). Coincidently, we found that Liz expression peaks at meiosis during mouse spermatogenesis, and canonical Zdbf2 is highly transcribed in the oocyte, leading to the exciting possibility that Zdbf2 may fulfill meiotic roles in mammals.…”
Section: Discussionmentioning
confidence: 73%
“…There is a high frequency of dyad formation [34]. A similar naturally occurring C-terminal truncation mutant of dfp1 (rad35) was previously identified and was shown to be sensitive to DNA damages.…”
Section: Regulation Of Meiotic Recombination By Hsk1/cdc7mentioning
confidence: 98%
“…In fission yeast, the localization of the monopolin complex to kinetochores is not required for mono-orientation [42]. Rec8 phosphorylation by both CK1 (casein kinase 1) and Hsk1/Cdc7 is a prerequisite for the cleavage of Rec8 by separase in budding and fission yeasts [34,43,44].…”
Section: Regulation Of Meiotic Cell Division By Hsk1/cdc7 and Relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, 2 kinases phosphorylate Rec8 to promote the cleavage of cohesin on chromosome arms at anaphase I: Hrr25, a conserved casein kinase 1d, and the Dbf4dependent Cdc7 kinase. [21][22][23] Accordingly, inhibition of both kinases or mutations of Rec8 phospho-sites blocks Rec8 cleavage and homolog disjunction. 22 Protection of centromeric Rec8 from cleavage by separase at anaphase I depends on orthologues of the Drosophila Mei-S332 protein, known as shugoshins (Sgo).…”
Section: Introductionmentioning
confidence: 99%